RETROFIT SPEED CONTROL ACTUATOR BOILER FEED PUMP TO IMPROVE STEAM POWER PLANT RELIABILITY - Mawardi, Muhammad (Universitas Muhammadiyah Semarang, 2024)
A Boiler Feed Pump (BFP) is a very important equipment in Steam Power Plants (PLTU), which functions to pump water from the feedwater tank to the boiler drum. If the BFP experiences a disturbance, the PLTU will experience derating or shutdown. For one year, there were repeated disruptions to BFP, causing the plant to experience an unplanned shutdown (Forced Outage/FO). Analysis of disturbance data was carried out to find the root cause of the problem of repeated disturbances in BFP, using the Root Cause Failure Analysis (RCFA) method. RCFA results show that the cause of repeated interference in BFP is a problem with the Speed Control Actuator which uses an Analog Electric Actuator (Motorized) as a Hydraulic Coupling drive. The main disadvantages of the Analog Electric Actuator system are low response speed, easily changing settings, motor protection often fails and the module often hangs. The solution to this problem is to carry out a retrofit to replace the BFP actuator speed control from an Analog Electric Actuator system to a Digital Electro Pneumatic system.. The retrofit was successfully performed on BFP 1A and proved to be able to operate normally without interruption during the period of operation. After a successful retrofit was performed on BFP 1A, the retrofit was also performed on all other BFPs, namely BFP 2B, 2A, and 1B. Overall, retrofit proved to be able to overcome the weaknesses of the Analog Electric Actuator system and improve the reliability of the power plant. Financially, retrofits eliminate corrective maintenance costs of actuator replacement and eliminate potential plant losses due to lost production opportunities.